The Relationship Between Sense of Community and Academic Procrastination in Students of SMK Antartika 2 Sidoarjo: Hubungan Antara Sense Of Community dan Prokrastinasi Akademik pada Siswa SMK Antartika 2 Sidoarjo - Ardiyan, Muh Bintang; Affandi, Ghozali Rusyid (UMSIDA Preprints Server, 2023)
This study aims to determine the relationship between sense of community and academic procrastination. This type of research is quantitative using a correlational approach. The study population was students of SMK Antarctica 2 Sidoarjo, totaling 2,470 students. The sample of this study amounted to 304 students using proportional stratified random sampling technique. . The research data collection technique used a sense of community scale and an academic procrastination scale. The data analysis technique uses Pearson's product moment correlation . The results of data analysis showed a negative correlation between sense of community and academic procrastination in students of Antarctica 2 Sidoarjo Vocational School. This can be proven by the correlation coefficient of -0.276 with a significance level of 0.000, so that the hypothesis that can be proposed in this study can be accepted, where if the sense of community increases, academic procrastination decreases. And vice versa.